Limiting resource and leaf functional traits jointly determine distribution patterns of leaf intrinsic water use efficiency along aridity gradients - Wang, Jing; Wen, Xuefa (Frontiers in Plant Science, 2022)
Intrinsic water use efficiency (iWUE) is a critical eco-physiological function allowing plants to adapt to water- and nutrient-limited habitats in arid and semi-arid regions. However, the distribution of iWUE in coexisting species along aridity gradients and its controlling factors are unknown. We established two transects along an aridity gradient in the grasslands of Losses Plateau (LP) and Inner Mongolia Plateau (MP) to elucidate the patterns and underlying mechanisms of iWUE distribution in coexisting species along aridity gradient. We determined leaf carbon (δ13C) and oxygen (δ18O) stable isotopes, functional traits related to carbon fixation, and limiting resources. Bulk leaf δ13C and δ18O were used as proxies for time-integrated iWUE and stomatal conductance (gs) during the growing season. Our results showed that variability in iWUE within transect was primarily controlled by species, sampling sites and an interactive effect between species and sampling sites. Mean values of iWUE (iWUEMean) increased and coefficient of variation (CV) in iWUE (iWUECV) decreased with an increase in aridity, demonstrating that increases in aridity lead to conservative and convergent water use strategies. Patterns of iWUEMean and iWUECV were controlled primarily by the ratio of soil organic carbon to total nitrogen in LP and soil moisture in MP. This revealed that the most limited resource drove the distribution patterns of iWUE along aridity gradients. Interspecific variation in iWUE within transect was positively correlated with △18O, indicating that interspecific variation in iWUE was primarily regulated by gs. Furthermore, relationship between iWUE and multi-dimensional functional trait spectrum indicated that species evolved species-specific strategies to adapt to a harsh habitat by partitioning limiting resources. Overall, these findings highlighted the interactive effects of limiting resources and leaf functional traits on plant adaptation strategies for iWUE, and emphasized the importance of considering biological processes in dissecting the underlying mechanisms of plant adaptation strategies at large regional scales.